2020
DOI: 10.3390/s20051244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Full Body Motion Recognition Camera Interaction and Hand Controllers Interaction used in Virtual Reality Exposure Therapy for Acrophobia

Abstract: Virtual Reality has already been proven as a useful supplementary treatment tool for anxiety disorders. However, no specific technological importance has been given so far on how to apply Virtual Reality with a way that properly stimulates the phobic stimulus and provide the necessary means for lifelike experience. Thanks to technological advancements, there is now a variety of hardware that can help enhance stronger emotions generated by Virtual Reality systems. This study aims to evaluate the feeling of pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Additional controlled trials [87][88][89][90][91][92][93][94][95] compared the effects of virtual exposure and in vivo exposure, and two special studies [88,91] compared the differences between self-help virtual therapy and therapist-guided therapy. There have been a number of secondary studies, including literature reviews [72,78,[96][97][98][99][100][101][102][103][104], systematic reviews [105,106], and meta-analyses [107][108][109][110][111][112][113][114][115][116][117][118], that evaluated the efficacy of VR. Moreover, various studies [98,106,111,115,118] have explored the mechanism of VR-aided therapy by reviewing moderated factors of outcome, such as presence, therapy alliance, cognition process, and therapy duration.…”
Section: Anxiety and Fear Related Disorder (Aandf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional controlled trials [87][88][89][90][91][92][93][94][95] compared the effects of virtual exposure and in vivo exposure, and two special studies [88,91] compared the differences between self-help virtual therapy and therapist-guided therapy. There have been a number of secondary studies, including literature reviews [72,78,[96][97][98][99][100][101][102][103][104], systematic reviews [105,106], and meta-analyses [107][108][109][110][111][112][113][114][115][116][117][118], that evaluated the efficacy of VR. Moreover, various studies [98,106,111,115,118] have explored the mechanism of VR-aided therapy by reviewing moderated factors of outcome, such as presence, therapy alliance, cognition process, and therapy duration.…”
Section: Anxiety and Fear Related Disorder (Aandf)mentioning
confidence: 99%
“…There have been a number of secondary studies, including literature reviews [72,78,[96][97][98][99][100][101][102][103][104], systematic reviews [105,106], and meta-analyses [107][108][109][110][111][112][113][114][115][116][117][118], that evaluated the efficacy of VR. Moreover, various studies [98,106,111,115,118] have explored the mechanism of VR-aided therapy by reviewing moderated factors of outcome, such as presence, therapy alliance, cognition process, and therapy duration. Anderson and Molloy [96] shed light on the safety, technical advantages, and acceptance of VR, and further studies [99,104,105,114] identified the main challenges of promoting VR and assessed the regularity of common applications.…”
Section: Anxiety and Fear Related Disorder (Aandf)mentioning
confidence: 99%
“…Geliştirdikleri yeni ara yüz tasarımı ile hem başa takılan görüntüleyiciler ile gerçekleştirilen hem de sadece el kontrolcüleri ile gerçekleştirilen sanal gerçeklik uygulamalarında yaşanan bulunma hissi düzeyinin arttığı tespit edilmiştir. Katılımcıların sanal gerçeklik ortamını deneyimlemeleri sırasındaki hareketlerini inceleyen bir başka çalışmada ise tüm vücut hareketlerinin takip edildiği kameralar ile yapılan sanal gerçeklik uygulamasının sadece ellerin kontrol edildiği uygulamaya kıyasla daha yüksek bulunma hissi sağladığı belirlenmiştir (Kritikos ve diğerleri, 2020). Çok yakın dönemde yapılan dikkate değer araştırmalardan biri ise yeni geliştirilen kablosuz başa takılan görüntüleyiciler ile kabloluların karşılaştırılması olmuştur.…”
Section: Bulunma Hissi üZerine Teknik İncelemelerunclassified
“…Concerning the best interaction modalities, the research of Kiritikos et al [17] showed that the highest feeling of presence was obtained while using Motion Recognition Cameras, compared to Hand Controller systems, for 20 study participants, in a virtual environment on the topic of acrophobia. The subjects had to execute three consecutive taskswalk across a room and exit on the balcony, reach the balcony railing and catch an object hanging at a particular distance from the balcony's railing.…”
Section: Related Workmentioning
confidence: 99%